The development of intervention nursing in China - Yang Xu; Xuemei Wang; Yongde Cheng (Journal of Interventional Medicine, 2019)
Intervention nursing emerged in China in the 1980s. It has been developing rapidly since then, along with interventional radiology, and has become an indispensable professional discipline in clinical nursing. In this paper, the author focuses on the initiation and development of intervention wards in a Chinese context and how the development of the topic in scientific research, periodical publications, and academic exchanges shows that intervention nursing in China is moving toward specialization, standardization, and scientificalization, and is gradually getting known in the international intervention nursing community via these international conferences which provide a platform for the exchange of innovative ideas. Keywords: Interventional radiology, Intervention nursing, China, Development